Science: Maintaining the purity of the reading of the Qur'an - Nada Ramadhania; Mariza Laili; Muhammad Ade Rizky; Edi Hermanto (Islamic Studies in the World, 2024)
Background. Tahsin science is a branch of knowledge in Islamic studies which aims to maintain the purity and beauty of the reading of the Koran. In this context, tahsin comes from the Arabic word which means "repair" or "beautify". The importance of tahsin lies in its efforts to ensure that every Muslim reads the Koran according to the correct tajwid and makhraj. Tajwid is the science that regulates how to pronounce the letters in the Koran correctly, while makhraj refers to the place where the letters appear. Purpose. This journal examines the importance of tahsin knowledge in maintaining the purity of Al-Qur'an reading. Method. This research methodology includes literature studies, interviews with tahsin experts, and direct observation of the tahsin teaching process in several Islamic educational institutions. Results. The research results show that effective tahsin training can improve the quality of Al-Qur'an reading, reduce errors in pronunciation, and increase understanding of the meaning of Al-Qur'an verses. In addition, this research found that there are several challenges in teaching tahsin, including a lack of competent teachers, limited time in the formal education curriculum, and a lack of motivation among students. Therefore, efforts are needed to improve training for tahsin teachers, introduce tahsin programs in the school curriculum, and develop interesting and interactive teaching methods. Conclusion. The conclusion of this research emphasizes that tahsin science has a very important role in maintaining the purity of Al-Qur'an reading and must be a priority in Islamic education. Continuous efforts are needed to ensure that every Muslim is able to read the Qur'an correctly and beautifully, in accordance with the guidance of tajwid and makhraj. Background. Tahsin science is a branch of knowledge in Islamic studies which aims to maintain the purity and beauty of the reading of the Koran. In this context, tahsin comes from the Arabic word which means "repair" or "beautify". The importance of tahsin lies in its efforts to ensure that every Muslim reads the Koran according to the correct tajwid and makhraj. Tajwid is the science that regulates how to pronounce the letters in the Koran correctly, while makhraj refers to the place where the letters appear. Purpose. This journal examines the importance of tahsin knowledge in maintaining the purity of Al-Qur'an reading. Method. This research methodology includes literature studies, interviews with tahsin experts, and direct observation of the tahsin teaching process in several Islamic educational institutions. Results. The research results show that effective tahsin training can improve the quality of Al-Qur'an reading, reduce errors in pronunciation, and increase understanding of the meaning of Al-Qur'an verses. In addition, this research found that there are several challenges in teaching tahsin, including a lack of competent teachers, limited time in the formal education curriculum, and a lack of motivation among students. Therefore, efforts are needed to improve training for tahsin teachers, introduce tahsin programs in the school curriculum, and develop interesting and interactive teaching methods. Conclusion. The conclusion of this research emphasizes that tahsin science has a very important role in maintaining the purity of Al-Qur'an reading and must be a priority in Islamic education. Continuous efforts are needed to ensure that every Muslim is able to read the Qur'an correctly and beautifully, in accordance with the guidance of tajwid and makhraj.